Assessing selection signatures within and between selected lines of dual‐purpose black and white and German Holstein cattle. (25th February 2020) - Naderi, S.; Moradi, M. H.; Farhadian, M.; Yin, T.; Jaeger, M.; Scheper, C.; Korkuc, P.; Brockmann, G. A.; König, S.; May, K.
Summary: The aim of this study was to detect selection signatures considering cows from the German Holstein (GH) and the local dual‐purpose black and white (DSN) population, as well as from generated sub‐populations. The 4654 GH and 261 DSN cows were genotyped with the BovineSNP50 Genotyping BeadChip . The geographical herd location was used as an environmental descriptor to create the East‐DSN and West‐DSN sub‐populations. In addition, two further sub‐populations of GH cows were generated, using the extreme values for solutions of residual effects of cows for the claw disorder dermatitis digitalis. These groups represented the most susceptible and most resistant cows. We used cross‐population extended haplotype homozygosity methodology (XP‐EHH) to identify the most recent selection signatures. Furthermore, we calculated Wright's fixation index ( F ST ). Chromosomal segments for the top 0.1 percentile of negative or positive XP‐EHH scores were studied in detail. For gene annotations, we used the Ensembl database and we considered a window of 250 kbp downstream and upstream of each core SNP corresponding to peaks of XP‐EHH. In addition, functional interactions among potential candidate genes were inferred via gene network analyses. The most outstanding XP‐EHH score was on chromosome 12 (at 77.34 Mb) for DSN and on chromosome 20 (at 36.29–38.42 Mb) for GH. Selection signature locations harbored QTL for several economically important milk and meat quality traits, reflecting the different breeding goals for GH and DSN. The average F ST value between GH and DSN was quite low (0.068), indicating shared founders. For group stratifications according to cow health, several identified potential candidate genes influence disease resistance, especially to dermatitis digitalis.